The discursive memories that emerge from the discourse of the Pedagogical Project of a technical course linked to Pronatec Campo at the IFTO, Campus Araguatins-TO - Jorlan Lima Oliveira (Universidade Federal do Norte do Tocantins, 2020)
The aim of this research is to analyze the effects of meaning (discursive memories) that emerge from the discourse of the Pedagogical Project of the Technical Auxiliary Course in Agriculture, offered by the Federal Institute of Tocantins, Campus Araguatins between the years of 2013 and 2014, as part member of Pronatec Campo. This short course focused on providing basic knowledge regarding agricultural activities to peasants belonging to the settlements located in the municipality of Araguatins-TO and nearby Discourse Analysis was used as methodological foundation based on the studies of Pêcheux (1999) and Orlandi (1999). From the analysis it is highlighted that the statements refer to the discursive memories that evoke the technicist formation, in addition to linking the exercise of citizenship to productivity in a capitalist environment.